ROLE AND CONSTRAINT OF INTERNAL CONTROL TOWARD THE IMPLEMENTATION OF ACCOUNTING INFORMATION SYSTEM AUDIT BASED ON INFORMATION TECHNOLOGY - T - Titania (Universitas Jember, 2016)
The changes in information technology nowadays has influenced in many aspects, include the accounting system. In manual accounting, employees need to perform the whole accounting cycle manually on a periodic basis, while in computerized accounting; employees can use computer and accounting software to perform the job. By using AIS the tasks can perform easily and any kinds of report can be made easily. The changing in accounting system can impact the audit process. Audit need to adjust the system, both in audit process and personnel who conduct the audit. The personnel should have a good understanding of clients’ business process and knowledge about information technology, therefore audit will result in a good internal control. Internal control can detect whether organization’s objective can be achieved effectively and efficiently. The implementation of internal control on AIS audit meets some constraint namely need of continuous monitoring of internal control especially for network breakdown, hacked system, virus threatened, and difficulty tracing the audit trails.